Plasma thrombospondin 1 as a predictor of postoperative liver dysfunction. Issue 7 (13th April 2015) - Starlinger, P.; Haegele, S.; Wanek, D.; Zikeli, S.; Schauer, D.; Alidzanovic, L.; Fleischmann, E.; Gruenberger, B.; Gruenberger, T.; Brostjan, C.
<x xml:space="preserve">Abstract</x> Background Liver regeneration following liver resection involves a complex interplay of growth factors and their antagonists. Thrombospondin 1 has recently been identified as a critical inhibitor of liver regeneration by the activation of transforming growth factor β1 in mice, and preliminary data seem to confirm its relevance in humans. This study aimed to confirm these observations in an independent validation cohort. Methods Perioperative circulating levels of thrombospondin 1 were measured in patients undergoing liver resection between January 2012 and September 2013. Postoperative liver dysfunction was defined according to the International Study Group of Liver Surgery and classification of morbidity was based on the criteria by Dindo et al. Results In 85 patients (44 major and 41 minor liver resections), plasma levels of thrombospondin 1 increased 1 day after liver resection (mean 51·6 ng/ml before surgery and 68·3 ng/ml on postoperative day 1; P = 0·001). Circulating thrombospondin 1 concentration on the first postoperative day specifically predicted liver dysfunction (area under the receiver operating characteristic (ROC) curve 0·818, P = 0·003) and was confirmed as a significant predictor in multivariable analysis (Exp(B) 1·020, 95 per cent c.i. 1·005 to 1·035; P = 0·009). Patients with a high thrombospondin 1 concentration (over 80 ng/ml) on postoperative day 1 more frequently had postoperative liver dysfunction than those with a lower level (28 versus 2 per cent) and severe morbidity (44 versus 15 per cent), and their length of hospital stay was more than doubled (19·7 versus 9·9 days). Conclusion Thrombospondin 1 may prove a helpful clinical marker to predict postoperative liver dysfunction as early as postoperative day 1.